2022
DOI: 10.3390/mi13081160
|View full text |Cite
|
Sign up to set email alerts
|

Design of Metal-Based Slippery Liquid-Infused Porous Surfaces (SLIPSs) with Effective Liquid Repellency Achieved with a Femtosecond Laser

Abstract: Slippery liquid-infused porous surfaces (SLIPSs) have become an effective method to provide materials with sliding performance and, thus, achieve liquid repellency, through the process of infusing lubricants into the microstructure of the surface. However, the construction of microstructures on high-strength metals is still a significant challenge. Herein, we used a femtosecond laser with a temporally shaped Bessel beam to process NiTi alloy, and created uniform porous structures with a microhole diameter of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, a decrease in SV was reported with increasing viscosity of the oils. Several other studies 19,20 reported the increase in SA and decrease in SV with increasing silicone oil viscosity.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, a decrease in SV was reported with increasing viscosity of the oils. Several other studies 19,20 reported the increase in SA and decrease in SV with increasing silicone oil viscosity.…”
Section: Introductionmentioning
confidence: 85%
“…), femtosecond laser technology has the advantages of high precision, good controllability and applicability to different materials. Therefore, intelligent bionic design with the help of advanced manufacturing technologies and tools such as femtosecond laser machining is also a focus of future research ( Yong et al, 2015 ; Zhang et al, 2020 ; Fang et al, 2022 ; Yong et al, 2022 ; Zhang et al, 2022 ). 5) The structural and functional design can be coherent and consistent, and the functional design can be considered in conjunction with the natural optical properties of the creature, thus imparting a more aesthetic character.…”
Section: Discussionmentioning
confidence: 99%
“…), femtosecond laser technology has the advantages of high precision, good controllability and applicability to different materials. Therefore, intelligent bionic design with the help of advanced manufacturing technologies and tools such as femtosecond laser machining is also a focus of future research ( Yong et al, 2015 ; Zhang et al, 2020 ; Fang et al, 2022 ; Yong et al, 2022 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Roughness can be generated by either adding a textured layer (bottom-top) or removing a portion of the surface (top-bottom) [69,[90][91][92][93]. Subtractive methods include photolithography, soft lithography, laser ablation and etching techniques [43,47,[94][95][96][97][98][99][100]. Additive techniques include methods such as deposition (chemical vapor deposition, electrochemical deposition, liquid-phase deposition techniques), sol-gel methods, self-assembly and layerby-layer assembly [101][102][103][104][105][106][107].…”
Section: Surface Structurementioning
confidence: 99%